Incidence of asymptomatic bacteriuria and antibiotic sensitivity Pattern in pregnant women at tertiary care hospital, Nepal - Hari Narayan Purbey,; Alok Chandra Mahato,; Dharma Datta Subedi,; Nagendra Prasad Yadav,; Kshitiz Shrestha,; Gayatri Gharti Magar,; Aashish Ale,; Rekha Sah, (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Asymptomatic bacteriuria (ASB) in pregnancy is often overlooked, yet it can lead to serious maternal and fetal complications. The emergence of antibiotic resistance adds to its clinical significance. The study aimed to determine the incidence, bacterial isolates, antibiotic susceptibility pattern, and associated sociodemographic factors of ASB in pregnant women attending antenatal care. Materials and Methods: A cross-sectional study was conducted among 101 asymptomatic pregnant women at a tertiary care hospital. Midstream urine samples were collected and processed using the Kirby–Bauer disk diffusion method. Sociodemographic and risk factor data were obtained via questionnaire. Results: ASB prevalence was 10.9%, predominantly in women aged 21–30 years, gravida ≤2, with cattle-rearing occupations, and consuming adulterated food. Escherichia coli was the sole isolate. High sensitivity was observed to Ofloxacin, Linezolid, Amikacin, Amoxicillin–Clavulanic acid, Cefepime, Clindamycin, and Nitrofurantoin, while resistance was noted to Amoxicillin and Azithromycin. Conclusion: ASB remains a hidden but preventable cause of pregnancy-related complications. Age, parity, occupation, diet, and socioeconomic status are potential risk factors. Routine urine culture and sensitivity testing is recommended in antenatal care to guide targeted antibiotic therapy.